Work programme 2015 - (:unkn) unknown (Publications Office of the European Union, 2015)
Cedefop's work programme 2015 is consistent with its medium-term priorities and its mission as laid down in the Founding Regulation. Chapter 2 of this document describes the European policy context. "Chapters 3 to 5 present an overview of planned activities and projects by medium-term priority, while detailed descriptions can be found in Chapter 9. Chapter 6 summarises the various communication activities and Chapter 7 focuses on management and administrative issues followed by the risk management plan in Chapter 8. The annexes outline the agency's financial and human resources, its planned procurement and its performance measurement framework. They also inform on Cedefop's cooperation and on its planned publications and events." (Editor, BIBB-Doku)
Dt. Ausg. u.d.T.: Arbeitsprogramm 2015
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; EU-Bildungspolitik